2005
DOI: 10.1021/jp044197j
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of (HIO3) Isomers and the HO2 + IO Reaction Pathways

Abstract: The geometries, harmonic vibrational frequencies, relative energetics, and enthalpies of formation of (HIO3) isomers have been examined using quantum mechanical methods. At all levels of theory employed, MP2, B3LYP, and CCSD(T), the lowest energy structure is found to be the HOIO2 form, which shows particular stability. The two isomers HOOOI and HOOIO are closely located at the CCSD(T) level of theory. The higher energy structure is HIO3. The interisomerization transition states have been determined, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
7
28
0
1
Order By: Relevance
“…Comparison of the enthalpies of formation for CH 3 COIO 3 isomers with HIO 3 and CH 3 IO 3 isomers calculated previously by Drougas et al 2,6 is shown in Figure 3. The enthalpies of formation for HIO 3 and CH 3 IO 3 were calculated at CCSD(T) theory.…”
Section: Comparison Of Relative Stability Of Rio 3 (R=h Ch 3 Ch 3 mentioning
confidence: 82%
See 4 more Smart Citations
“…Comparison of the enthalpies of formation for CH 3 COIO 3 isomers with HIO 3 and CH 3 IO 3 isomers calculated previously by Drougas et al 2,6 is shown in Figure 3. The enthalpies of formation for HIO 3 and CH 3 IO 3 were calculated at CCSD(T) theory.…”
Section: Comparison Of Relative Stability Of Rio 3 (R=h Ch 3 Ch 3 mentioning
confidence: 82%
“…Several experimental studies reported recently the coupling of IO with the hydrogen peroxy, HO 2 , methylperoxy, CH 3 O 2 , trifluoromethylperoxy, CF 3 O 2 , and ethylperoxy, C 2 H 5 O 2 radicals and measured the corresponding rate coefficients. 2,6,8 These systems are analogous to the reactions of HO 2 and CH 3 O 2 with the ClO and BrO radicals for which several experimental and theoretical studies have been reported. [9][10][11] It was found that the reaction of HO 2 +IO 12 displayed a rate coefficient, k= (8.4±0.3)×10 -11 cm 3 •molecule -1 •s -1 at 298 K and Drougas et al 6 suggested that the HO 2 and IO reaction proceed through the formation of the bound complexes, HOOOI and HOOIO.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations